2006
DOI: 10.1161/01.res.0000233317.70421.03
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Unfolded Protein Response in Infarcted Mouse Heart and Hypoxic Cultured Cardiac Myocytes

Abstract: Abstract-Endoplasmic reticulum (ER) stresses that reduce ER protein folding activate the unfolded protein response (UPR). One effector of the UPR is the transcription factor X-box binding protein-1 (XBP1), which is expressed on ER stress-mediated splicing of the XBP1 mRNA. XBP1 induces certain ER-targeted proteins, eg, glucose-regulated protein 78 (GRP78), that help resolve the ER stress and foster cell survival. In this study, we determined whether hypoxia can activate the UPR in the cardiac context. Neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
243
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(274 citation statements)
references
References 48 publications
20
243
2
9
Order By: Relevance
“…Hypoxia induces the expression of XBP1 splicing and GRP78 in cultures of rat neonatal cardiac myocytes [5,8]. In a mouse model of myocardial infarction, an increased expression of GRP78 was observed in cells near the infarct four days after occlusion of the left anterior descending coronary artery [5]. However, in our study, we found that the levels of GRP878 increased after 35 min ischemia followed by 60 min of reperfusion and after 24 hours of Tm treatment in cultured myocytes.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Hypoxia induces the expression of XBP1 splicing and GRP78 in cultures of rat neonatal cardiac myocytes [5,8]. In a mouse model of myocardial infarction, an increased expression of GRP78 was observed in cells near the infarct four days after occlusion of the left anterior descending coronary artery [5]. However, in our study, we found that the levels of GRP878 increased after 35 min ischemia followed by 60 min of reperfusion and after 24 hours of Tm treatment in cultured myocytes.…”
Section: Discussioncontrasting
confidence: 75%
“…However, few studies have investigated the role of ER stress in the induction of apoptosis during ischemia/ reperfusion. Hypoxia induces the expression of XBP1 splicing and GRP78 in cultures of rat neonatal cardiac myocytes [5,8]. In a mouse model of myocardial infarction, an increased expression of GRP78 was observed in cells near the infarct four days after occlusion of the left anterior descending coronary artery [5].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations